Skeletal muscle fibers produce B-cell stimulatory factors in chronic myositis - Carstens, Per-Ole; Müllar, Luisa M.; Wrede, Arne; Zechel, Sabrina; Wachowski, Martin M.; Brandis, Almuth; Krause, Sabine; Zierz, Stephan; Schmidt, Jens (Frontiers in Immunology, 2023)
Introduction We aimed to identify B-cell-mediated immunomechanisms in inclusion body myositis (IBM) and polymyositis (PM) as part of the complex pathophysiology. Materials and methods Human primary myotube cultures were derived from orthopedic surgery. Diagnostic biopsy specimens from patients with IBM (n=9) and PM (n=9) were analyzed for markers of B cell activation (BAFF and APRIL) and for chemokines that control the recruitment of B cells (CXCL-12 and CXCL-13). Results were compared to biopsy specimens without myopathic changes (n=9) and hereditary muscular dystrophy (n=9). Results The mRNA expression of BAFF, APRIL, and CXCL-13 was significantly higher in IBM and PM compared to controls. Patients with IBM displayed the highest number of double positive muscle fibers for BAFF and CXCL-12 (48%) compared to PM (25%), muscular dystrophy (3%), and non-myopathic controls (0%). In vitro, exposure of human myotubes to pro-inflammatory cytokines led to a significant upregulation of BAFF and CXCL-12, but APRIL and CXCL-13 remained unchanged. Conclusion The results substantiate the hypothesis of an involvement of B cell-associated mechanisms in the pathophysiology of IBM and PM. Muscle fibers themselves seem to contribute to the recruitment of B cells and sustain inflammation.